Impact of Sled-Integrated Resisted Sprint Training on Sprint and Vertical Jump Performance in Young U-14 Male Football Players - Manuel Amore; Diego Minciacchi; Giulia Panconi; Sara Guarducci; Riccardo Bravi; Vincenzo Sorgente (Journal of Functional Morphology and Kinesiology)
Background/Objectives: The aim of this study was to investigate the effects of a six-week integrated resisted sprint training (IRST) program on sprint performance and vertical jump height in a sample of U-14 male football players. This study also explored the potential benefits of incorporating variable resistive loads during pre-peak height velocity (pre-PHV) developmental stages, a period often overlooked in the training of young athletes. The IRST program alternated between heavy and light resistive sled loads to enhance sprint and jump capabilities, which are critical components of athletic performance in football. Methods: Nineteen healthy male football players (age: 13 ± 0.63 years) were divided into an experimental group (E, n = 10) and a control group (C, n = 9). The experimental group followed the IRST protocol, involving sled sprints with varying resistive loads (10–115% of the body mass) over specific distances, while the control group engaged in traditional unresisted sprint training. The sprint performance was assessed using 30 m sprint times, and the vertical jump height was measured using countermovement jump (CMJ) data collected via a force platform. Anthropometric measures and peak height velocity (aPHV) estimates were also recorded pre- and post-intervention. Results: The experimental group demonstrated significant improvements in 30 m sprint times (mean difference: −0.29 s; p < 0.01). Additionally, CMJ data revealed a positive trend in the take-off velocity and maximum concentric power, with an increase in jump height (mean difference: +0.44 cm). These results suggest enhanced sprint and explosive power capabilities following the IRST intervention. Conclusions: The findings suggest that the IRST program is an effective training method for enhancing sprint performance and maintaining jump capabilities in young football players. This approach highlights the importance of integrating variable resistance training in pre-PHV athletes to promote athletic development while ensuring safety and effectiveness.